Shona religious factors that promote resilience among people suffering from chronic illnesses - Mabvurira, Vincent (Penerbit Universiti Kebangsaan Malaysia, 2021)
The study aimed to assess Shona religious aspects that promote resilience among people suffering from chronic illnesses in Zimbabwe. The study adopted a qualitative approach and exploratory design. Data were collected through face to face in-depth interviews from 11 people. Findings pointed to the fact that the Shona cosmology notes the centrality of vadzimu in terms of life and death, good health and bad health and other vicissitudes of human life. Shona traditional beliefs and practices such as belief in afterlife, exorcism of evil spirits, traditional rituals, omnipresence of ancestors and many others were reported to strongly promote resilience among sick people. There is therefore need to recognise indigenous beliefs in social service delivery. Social workers should be culturally and spiritually competent for effective practice with certain indigenous African populations.